Avaliação do ciclo de vida de blocos estruturais e cerâmicos utilizados em alvenaria na construção civil. - Costa, Lourynny Hélia de Lima (Universidade Federal Rural do Semi-Árido, 2019)
The construction sector is considered as a major consumer of natural resources and cause of various environmental impacts. In this sense, there have been initiatives in the sector in recent years to improve the quality and increase the efficiency of its processes, including the development of more streamlined and industrialized building systems. However, the sector still lacks ways to assess the real environmental impacts of these different systems over their life cycles. Thus, this work addresses the use of the Life Cycle Assessment (LCA) technique performed using the SimaPro® 7.3 software for the production of ceramic blocks and concrete blocks used in masonry. The study was designed due to the need to provide new perspectives and a better knowledge of both LCA and the production and environmental impacts that generate the different types of blocks. This research intends to perform a life cycle assessment of ceramic blocks and concrete blocks, aimed at the use of sealing masonry, produced in two industries in the Northeast region, one in the state of Rio Grande do Norte and the other in the state of Paraíba. comparison of life cycle impacts between the two. An important step for interpreting LCA results was used in the life cycle impact analysis (LCIA) phase. The RECIPE assessment method uses weight distribution steps that result in an environmental impact indicator number of the product or process. in the data of an LCA. Thus, it is possible to highlight some critical points, such as the considerable consumption of non-renewable energy, as well as fossil fuels, the consequent contribution to global warming and toxicity to human health. And the results obtained by the RECIPE method showed that the ceramic block stands out among the studied blocks as being the most environmentally viable.
Keywords: Sustentabilidade; Gestão Ambiental; Edificações; Materiais; Sustainabilety; Environmental Management; Buildings; Materials; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA